mo_st_ : typophoto : moholy_nagy_studies. - Balla, Dóra (S.l. : MOME, 2015)
Bangó, Alexandra ; Batke, Bendegúz ; Boromissza, Katalin ; Buzás, Alíz ; Császár, Adrienn ; Csuport, Andrea ; Demecs, Fanni ; Elek, Gita ; Erdélui, Saroita ; Fazekas, Edina ; Földi, Viktor ; Gál, Enikö ; Gulyás, Benedek ; Horváth, Richárd ; Illés, Hajnaika ; Jákob, Bálint ; Kaszanyi, Nóra ; Kaszás, Balázs ; Kovács, Diána ; Kozma, Dániel ; Láng, Kristof ; Márton, Alex ; Mészáros, Lilla ; Molnár, Dávid ; Nagy, Zoltán ; Szatmári, Huba ; Szebenyi, Dávid ; Szörényi, Dávid ; Takács, Benedek ; Tóth, Teodóra ; Zsigó, Dániel
boek